2021
DOI: 10.5194/esurf-9-183-2021
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying thresholds of barrier geomorphic change in a cross-shore sediment-partitioning model

Abstract: Abstract. Barrier coasts, including barrier islands, beach-ridge plains, and associated landforms, can assume a broad spectrum of morphologies over multi-decadal scales that reflect conditions of sediment availability, accommodation, and relative sea-level rise. However, the quantitative thresholds of these controls on barrier-system behavior remain largely unexplored, even as modern sea-level rise and anthropogenic modification of sediment availability increasingly reshape the world's sandy coastlines. In thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 72 publications
1
7
0
Order By: Relevance
“…This work quantifies changes to the whole barrier system, including sandy (beach) and back-barrier (marsh and tidal flat) components, at annual to decadal scales, addressing knowledge gaps in decadal-scale barrier changes that result from incomplete historical records as well as the historical bias for focusing on shoreline and beach components without explicitly including the connectivity among barrier environments [1,101]. In doing so, we provide metrics that help better capture the timing and controls on the morphologic evolution of the northern Chandeleur Islands.…”
Section: Implications For Barrier-island Evolution and Resiliencymentioning
confidence: 99%
“…This work quantifies changes to the whole barrier system, including sandy (beach) and back-barrier (marsh and tidal flat) components, at annual to decadal scales, addressing knowledge gaps in decadal-scale barrier changes that result from incomplete historical records as well as the historical bias for focusing on shoreline and beach components without explicitly including the connectivity among barrier environments [1,101]. In doing so, we provide metrics that help better capture the timing and controls on the morphologic evolution of the northern Chandeleur Islands.…”
Section: Implications For Barrier-island Evolution and Resiliencymentioning
confidence: 99%
“…For instance, model simulations have shown that barrier islands with closed sediment budgets will experience shoreface flattening and island narrowing as sea levels rise (Lorenzo‐Trueba & Ashton, 2014; Passeri et al., 2020). Declining sediment availability further accelerates this process and may drive equivalent state changes in neighboring barrier islands (Ciarletta et al., 2021). Historical barrier island state changes have been documented for Cedar, Hog, and Parramore islands off the coast of Virginia, which transitioned to low elevation, erosional states during periods of higher relative SLR punctuated by storms (Dueser et al., 1976; Raff et al., 2018; Shawler et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Barrier islands are highly dynamic landforms shaped by wind, waves, water levels, currents, and vegetation (Davis jr, 1994; Leatherman, 1983). As a result of these forces, barrier islands experience nearly constant alterations to the shoreline and subaerial footprint (Dolan et al., 1988; Morton & Sallenger, 2003; Philips, 2017), with evolution constrained by sediment availability and human modifications to the landscape (Armstrong & Lazarus, 2019; Ciarletta et al., 2021; Hapke et al., 2010; Lorenzo‐Trueba & Ashton, 2014). Highly complex relations among natural disturbance regimes, substrates, and biological communities present on a barrier island can lead to equilibrium conditions in geomorphology and ecological community composition that can remain stable over centennial or millennial time scales (Ahnert, 1994; Cooper et al., 2007; Holling, 1973; Stallins, 2006; Zinnert et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Field and modeling studies have demonstrated that mesoscale barrier dynamics, defined as barrier-lagoon behavior at decadal/centennial timescales and meter to kilometer spatial scales (Cooper et al, 2018;Sherman, 1995), are primarily controlled by sediment accommodation and availability (Brenner et al, 2015;Ciarletta et al, 2021;Cooper et al, 2018;Psuty, 2008;Raff et al, 2018;Shawler et al, 2021a). These drivers are in turn a function of antecedent topography (e.g., pre-transgressive surface morphology; Shawler et al, 2021a); inlet dynamics (Nienhuis and Lorenzo-Trueba, 2019); climate and vegetation (Jackson et al, 2019;Mendes and Giannini, 2015); and relict or "inherited" morphology (Timmons et al, 2010).…”
Section: Introductionmentioning
confidence: 99%